Przemyśleć na nowo Europę - Dziuba, Andrzej F. (Społeczeństwo, 2022)
On 27-29 October 2017, the New Synodal Hall held the International Conference: „Reconsidering Europe. The Christian contribution to the future of the European project”. The Conference was organized by the Vatican Secretariat of State and the Commission of the Bishops’ Conferences of the European Community (COMECE) with the support of Renovabis. It was a broad debate with a pretty significant variety of topics. The pope himself indicated that during the conference „young people were able to present their expectations and hopes, confront with older people who, on the other hand, had the opportunity to offer their rich experience and reflections”.